2023
DOI: 10.1039/d2ra07164a
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid saponins and C21 steroidal glycosides from Gymnema tingens and their glucose uptake activities

Abstract: Four new triterpenoid saponins, tigensides A–D (1–4), and one new C21 steroid, tipregnane A(9), together with six known compounds were isolated from the EtOAc fraction of the roots and stems of Gymnema tingens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…El Barky et al (2017) also reported saponin decreases serum blood glucose levels in diabetic patients. Saponin exhibited a hypoglycemic effect in type 2 diabetic mice (Chai et al, 2021) by increasing glucose uptake activities (He et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…El Barky et al (2017) also reported saponin decreases serum blood glucose levels in diabetic patients. Saponin exhibited a hypoglycemic effect in type 2 diabetic mice (Chai et al, 2021) by increasing glucose uptake activities (He et al, 2023).…”
Section: Resultsmentioning
confidence: 99%